2000
DOI: 10.1098/rspb.2000.1085
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone treatment is immunosuppressive in superb fairy–wrens, yet free–living males with high testosterone are more immunocompetent

Abstract: The immunocompetence handicap hypothesis proposes that the immunosuppressive e¡ect of testosterone enforces honesty of sexual signalling via a physiological trade-o¡ between signal intensity and immunocompetence. However, evidence that testosterone is immunosuppressive is scant, particularly in birds. I studied the correlation between immunocompetence and testosterone in superb fairy-wrens (Malurus cyaneus), a species with intense intersexual selection. Males are seasonally dichromatic and testosterone increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
155
3
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(166 citation statements)
references
References 31 publications
7
155
3
1
Order By: Relevance
“…Previous studies have shown that the acquisition and maintenance of nuptial plumage in fairy-wrens is dependent on elevated testosterone levels (Peters et al , 2001, which compromise immunocompetence; though consistent with honest signalling theory, highquality males are better able to regulate immunocompetence (Peters 2000). Whether sustaining blue plumage for a long time imposes viability costs is extremely difficult to test, as a male can only be defined as not having moulted by virtue of its survival in eclipse plumage, biasing analysis to conclude that early moulting imposes a cost.…”
Section: Costs Of Sexual Signallingmentioning
confidence: 86%
See 1 more Smart Citation
“…Previous studies have shown that the acquisition and maintenance of nuptial plumage in fairy-wrens is dependent on elevated testosterone levels (Peters et al , 2001, which compromise immunocompetence; though consistent with honest signalling theory, highquality males are better able to regulate immunocompetence (Peters 2000). Whether sustaining blue plumage for a long time imposes viability costs is extremely difficult to test, as a male can only be defined as not having moulted by virtue of its survival in eclipse plumage, biasing analysis to conclude that early moulting imposes a cost.…”
Section: Costs Of Sexual Signallingmentioning
confidence: 86%
“…However, overwhelmingly the best predictor of female choice is a display of endurance (sensu Payne & Pagel 1996), the amount of time prior to the start of the breeding season that males are adorned in nuptial plumage, which in turn predicts the time those males have spent in frequent extra-territorial excursions to display to the neighbouring females (Dunn & Cockburn 1999;Green et al 2000;. The trait has been demonstrated to have adverse physiological consequences, and all available data support a hypothesis of strong condition dependence (Peters 2000;Peters et al 2000Peters et al , 2001. The trait varies dramatically between individuals, as some males can bear nuptial plumage and display throughout the winter, while most acquire nuptial plumage only in the late winter or early spring, months after their early moulting counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, exogenous administration of testosterone was shown to inhibit the transition from mating to paternal behavior, and to promote polygynous mating strategies in monogamous biparental populations of various passerine species (Silverin, 1980;Wingfield, 1984b;Hegner and Wingfield, 1987;Dittami et al, 1991;Ketterson and Nolan, 1992;De Ridder et al, 2000). However, a hormonal signal may not only interact with behavior, physiology, and morphology, but in addition, it may involve potential "costs" in terms of overall fitness, such as direct and indirect energetic costs, immunosuppression, increased mortality, and reproduction failure (Marler and Moore, 1988;Dufty, 1989;Wingfield, 1990;Ros et al, 1997;Wingfield et al, 1999a;Peters, 2000). As these changes in fitness occur where the same hormone mediates antagonistic traits, androgens can be viewed as physiological mediators of the trade-off between investment in male-male competition or in paternal care (Hegner and Wingfield, 1987;Ketterson and Nolan, 1992).…”
mentioning
confidence: 99%
“…Males may differ in their ability of coping with pathogens due to variation in individual condition, which may mask the immunosuppressive effect of androgens (e.g., Peters, 2000). A critical test of the immunocompetence handicap therefore requires the manipulation of androgen levels (Roberts et al, 2004).…”
mentioning
confidence: 99%